Thermodynamics, molecular modelling and denaturation studies on exploring the binding mechanism of tetramethylpyrazine with human serum albumin. (January 2020) - Khatun, Samima; Riyazuddeen,; Kumar, Amarjeet; Subbarao, Naidu
Highlights: ITC revealed that TMPZ binds to HSA through hydrogen bonding and van der Waals forces. Molecular docking showed that TMPZ binds near sub-domain IIA of HSA. Both HSA and HSA-TMPZ systems are similar throughout the 50 ns MD simulation. TMPZ inhibits the esterase activity of HSA in a competitive manner. Denaturation study proved that TMPZ decreases the stability of HSA. Abstract: Tetramethylpyrazine (TMPZ), a Chinese herb effectively used for cardiovascular disorders. The present study reports in vitro interaction studies of TMPZ with human serum albumin (HSA) using various spectroscopic, isothermal titration calorimetric (ITC), molecular modelling studies. The association constant ( K a ), standard enthalpy change (Δ H° ), standard entropy change ( ΔS° ) and standard Gibbs free energy change (Δ G° ) were obtained from ITC. The thermodynamic investigations suggest that the interaction of HSA and TMPZ is an exothermic process and enthalpy driven. Far-UV CD spectroscopy has been applied to check the stability of HSA in presence of TMPZ under thermal and chemical denaturant condition. Molecular docking was performed to confirm the binding site of TMPZ on HSA and amino acids involved in the binding process and it is found that TMPZ binds at Sudlow site I of HSA. Comparative MD simulation study of HSA and HSA-TMPZ complex shows that the structure of HSA in both systems is stable and has almost similar properties. The binding free energies calculated from the molecular mechanics/Poisson-Boltzmann surface area (MM-PBSA) method showed that van der Waals forces are the predominant intermolecular forces. Esterase-like activity of HSA decreases in the presence of TMPZ. Thus, this study will provide useful information regarding the interaction of TMPZ with HSA, helping to understand the activity and mechanism of drug binding and highlights its importance in the clinical medicine.